2022
DOI: 10.1111/jocd.14797
|View full text |Cite
|
Sign up to set email alerts
|

Global incidence and prevalence of bullous pemphigoid: A systematic review and meta‐analysis

Abstract: Background Integrated information on the global prevalence and incidence of bullous pemphigoid (BP) is lacking. Objective To estimate the incidence and prevalence of BP in a systematic review and meta‐analysis. Methods Observational studies were included by using databases of Medline, EMBASE, and Cochrane Library. Subgroup analysis was by continent, age, sex, and country income level. Random‐effects model was used. Between‐study heterogeneity was assessed using the I2 statistic. Results The global incidence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 96 publications
(279 reference statements)
0
14
0
Order By: Relevance
“…Age is frequently seen as a risk factor for BP (54). According to several previous studies, the prevalence of BP rises progressively and considerably with age in the general population, notably in people over 70 (3,(62)(63)(64). According to Lu et al, age-specific incidence increased across all age groups.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Age is frequently seen as a risk factor for BP (54). According to several previous studies, the prevalence of BP rises progressively and considerably with age in the general population, notably in people over 70 (3,(62)(63)(64). According to Lu et al, age-specific incidence increased across all age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Clinically, patients with BP often present with tense blister formation and symptoms of severe pruritus over urticarial plaques on the trunk and extremities (2). According to by Lu et al, the overall incidence was 4.19 per 100 000 person-years (3). Additionally, the prevalence of BP rises dramatically with aging and is most common among the elderly (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence of bullous pemphigoid is 0.0419 per 1000 person-years. 6 BP has been reported to be significantly associated with mortality, with 1-year mortality rates ranging from 6% to 41%. 7 Two studies based on Chinese hospitals reported 1-year mortality rates of 12.9% and 23.4%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Bullous pemphigoid belongs to a group of subepidermal autoimmune blistering diseases, mainly affects elderly persons over 65 years of age, and is characterized by damage to the protein constituents of the basement membrane zone (BMZ). The incidence of BP is 6 times higher in North America and Europe when compared to Asia ( Lu et al, 2022 ). The pathogenesis of BP is associated with the presence of autoantibodies directed againts hemidesmosomal proteins: BP antigen 2 (BPAG2/BP180, a transmembrane glycoprotein, type VII collagen) and the intracellular BP antigen 1 (BPAG1/BP230) located on the BMZ in the skin and mucous membranes ( Kayani and Aslam, 2017 ).…”
Section: Diseases Where Self-reactive Ige Is Known To Have a Pathogen...mentioning
confidence: 99%